Upregulation of nuclear factor‐κB activity mediates CYP24 expression and reactive oxygen species production in indoxyl sulfate‐induced chronic kidney disease. Issue 9 (September 2016) - Wang, Lihua; Gao, Zhiying; Wang, Lili; Gao, Yongning
Abstract: Aim: Chronic kidney disease (CKD) is associated with an inflammation‐mediated process, and the vitamin D (3) catabolizing enzyme, CYP24, is frequently overexpressed in CKD, where it may play a crucial role in kidney disease. Methods: Herein, in this study, we investigated CYP24, reactive oxygen species (ROS), and inflammatory responses in an indoxyl sulfate (IS)‐induced CKD model to elucidate the role of CYP24 in CKD. Results: Our results showed that IS upregulates proinflammatory cytokine, CYP24 and nuclear factor‐κB (NF‐κB) expression in human renal proximal tubule epithelial cells. In addition, IS treatment increased ROS production and simultaneously upregulated CYP24 expression and NF‐ κ B translocation. Moreover, the IS‐induced upregulation of CYP24 expression was alleviated by an inhibitor of NF‐κB, as well as a siRNA specific to NF‐κB p65. Furthermore, the renal cortex of DN (Dahl salt‐resistant normotensive) + IS, DH (Dahl salt‐sensitive hypertensive), and DH + IS rats showed increased expression of NF‐κB p65, CYP24, 8‐hydroxydeoxyguanosine (8‐OHdG), a marker of ROS and macrophage infiltration compared with DN rats. Conclusions: These results provide evidence that administration of IS in human renal tubular epithelial cells upregulates NF‐κB, which leads to increase CYP24 expression and ROS production. They also suggest that suppressing NF‐ κ B signalling is promising for the development into a strategy for CKD treatment. Summary at a Glance: Studies from Wang et al have examined the in vitro and in vivo effects of the uraemic toxin indoxyl sulfate. Their work identifies potential mechanistic links between inflammation and CYP47, and therefore novel insights into the pathogenesis of CKD.